Managing cabin crew fatigue during ultra-long range operations - van den Berg, M. J.; Zaslona, J. L.; Muller, D. P.; Wu, L.; Hughes, M.; Johnston, B.; Dyer, C.; Drane, M.; Signal, T. L. (Frontiers in Environmental Health, 2023)
Introduction Ultra-long range (ULR) flights have the potential to increase fatigue-related risk for cabin crew, if the extended flight times are associated with extended wakefulness, sleep loss and higher levels of crew fatigue. ULR flights may also require longer opportunities for recovery sleep. This study evaluates the utilization of fatigue risk mitigations for cabin crew operating the Auckland – Chicago ULR route with a two-day layover. Methods 65 cabin crew (45 women; aged 20–59 years) wore an actigraph and completed a sleep/duty diary for 3 local nights prior to, throughout, and for 3 local nights after a ULR trip. Crewmembers rated their fatigue (Samn-Perelli Crew Status Check), sleepiness (Karolinska Sleepiness Scale), and workload (OW; NASA-TLX) at key times during each flight. Jet lag was rated each day at home and during layover. Results Fatigue and sleepiness were highest at top-of-descent and after landing and were higher on the inbound flight than on the outbound flight. For every hour of additional sleep in-flight, top-of-descent fatigue ratings decreased by 0.24 points and top-of-descent sleepiness ratings decreased by 0.38, whereas top-of-descent fatigue and sleepiness ratings increased by 0.24 points with every 10-point increase in OW ratings. Crew slept more in the 24-hours prior to the outbound (M = 8.5 h) and inbound flights (M = 9.1 h) compared to pre-trip baseline days (M = 8.2 h). Post-trip, crew slept more during the first day (M = 9.9 h) compared to baseline, with 95% taking a daytime nap. Jet lag ratings decreased daily on return home but were still higher on the fourth day than on the day of the outbound flight. Discussion Cabin crew prepare for ULR flights by obtaining more sleep prior to departure. However, large individual differences in sleep and declining jet lag ratings across pre-trip days suggest that some crewmembers may still be recovering from a previous trip. Further refinement of in-flight sleep strategies and workload mitigations could be considered for managing fatigue risk at top-of-descent. Findings also highlight the importance of a protected period of post-trip rest to facilitate cabin crews' recovery from the effects of sleep restriction and circadian disruption associated with this ULR trip.